An Analysis of Teacher Talk in an EFL Classroom Interaction - Lulu Laelatunnuro; Hanif Nurcholish Adiantika; Dila Charisma (National Conference on Language, Education, and Technology Proceeding, 2021)
Teacher talk is important in classroom interaction because it can help students improve their comprehension of the learning materials and encourage them to be more active during the learning process. This research was aimed to analyze the categories of talk employed by the lecturer in the classroom interaction in English teaching and learning process at chemistry education in one private university in Cirebon based the framework FIACS (Flander’s Interaction Analysis Categories System). The lecturer at chemistry education in one private university in Cirebon was chosen as participant of this research. In this research, the researchers used qualitative descriptive method in collecting the data. The instruments of this research were observation as well video recording, observation sheet and structure interview. The findings reveals that the most dominant type used by the participant is asking question with 143 occurrences (35.57%), followed by Lecturing category with 98 occurrences (24.50%), accept or use idea of students category with 60 occurrences (15.00%), Giving directions category with 55 occurrences (13.25%), accept feelings category with 30 occurrences (7.50%), Praise or encourages category with 14 occurrences (3.50%), and the last is criticizing or justifying authority with 2 occurrences (0,50%) as the lowest category. According to the interview results, the participants employ those teachers talk categories in the teaching and learning interaction in the classroom to make the lesson more interactive, impressing, and relevant for everyone in the classroom, not just the participant, but also the students. Keywords: Classroom Interaction; Flander’s Interaction Analysis Categories System (FIACS); Teacher’s Talk.